Micropropagação de Bambusa vulgaris visando a produção de mudas clonais - Ribeiro, Anatálya dos Santos (2017)
Faced with the growing demand for products derived from woody biomass, bamboo species present interesting morphological and silvicultural characteristics and stand out as an alternative for the composition of forest plantations. However, due to the difficulty of producing large scale seedlings through traditional methods, this potential has not been explored. Therefore, the objective of the present work was to contribute to the improvement of the large - scale clonal multiplication of Bambusa vulgaris by means of the micropropagation technique. In the in vitro establishment, nodal segments of B. vulgaris were inoculated in MS liquid culture medium, where the effect of different solutions of a systemic and contact fungicide (0.5 and 1.0 mL) considering different exposure times (0, 72 and 120 hours). The explants considered established were transferred to a semi-solid MS culture medium containing 3 mg.L-1 BAP to analyze the residual effect of the fungicide along subcultures during multiplication and in vitro elongation of the explants. In the second experiment, established explants of B. vulgaris were transferred to three distinct culture systems (temporary immersion bioreactor, test tubes with stationary liquid culture medium, and semi-solid culture medium) combined with two concentrations of sucrose (0 and 30 g.L-1). During the experiment the number of explants, number of shoots per explant and average length of shoots per explant were evaluated. In the process vitro establishment, immersion of B. vulgaris explants in liquid culture medium containing 1 mL.L-1 of fungicide was highlighted with the best results. In vitro multiplication, explants immersed in liquid culture medium containing 1 mL of fungicide for 120 hours showed higher number of explants, percentage of explants that emitted shoots and average number of shoots per explant. The use of a bioreactor system with culture medium supplemented with 30 g.L-1 of sucrose provided during the in vitro multiplication the lowest rate of contamination, higher survival and higher rate of explants that emitted shoots.The combination of rooting induction culture medium, composed of 1 mg.L-1 IBA, 30 g.L-1 sucrose and 7 g.L-1 agar, and use of the mini-incubator system during ex vitro rooting were Effective in the formation of adventitious rooting. The presence of activated charcoal in the culture medium, during ex vitro rooting, increased the survival rate of the clones.